2016
DOI: 10.1007/s00705-016-3167-2
|View full text |Cite
|
Sign up to set email alerts
|

Expression of human endogenous retrovirus K and W in babies

Abstract: Here we determined the relative expression of HERV-K and W proviruses in HIV infected and non-infected mothers as well as their respective babies up to 1 year-old. HIV-infected mothers, their babies and uninfected control groups presented expression of both HERV-K and HERV-W with relatively high frequency. While the level of HERV-K expression was similar among groups, the level of HERV-W expression in HIV-infected mothers was four-fold higher than the uninfected mothers from the control group (p < 0.01). HERV-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…For what concerns the opposite scenario, Esqueda and coauthors observed a lack of correlation between HML2 expression and HIV-1 viral load in patients' plasma, especially after the careful removal of cellular DNA, which allowed accurate evaluation of HML2 RT-PCR signals [28]. Another study reported an absence of variation in HML2 RNA between infected and uninfected women, but observing an increase of HERV-W expression in HIV-infected mothers that was associated with a slight downregulation in HIV-exposed babies as compared to non-exposed ones [29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For what concerns the opposite scenario, Esqueda and coauthors observed a lack of correlation between HML2 expression and HIV-1 viral load in patients' plasma, especially after the careful removal of cellular DNA, which allowed accurate evaluation of HML2 RT-PCR signals [28]. Another study reported an absence of variation in HML2 RNA between infected and uninfected women, but observing an increase of HERV-W expression in HIV-infected mothers that was associated with a slight downregulation in HIV-exposed babies as compared to non-exposed ones [29].…”
Section: Discussionmentioning
confidence: 99%
“…Focusing on the possible effects of HIV infection on HERV transcription, current results are still discordant: on the one side there is a body of literature reporting that HIV infection increases the expression of endogenous elements [22][23][24][25][26][27] while, on the other side, a number of studies propose the absence of such stimulation by HIV [28,29]. It is worth noting that all these studies assess the overall, general expression of one or more genes of a given HERV group, i.e., without connecting the observed transcript to any specific locus and without information regarding primer specificity and cross-reactivity.…”
Section: Introductionmentioning
confidence: 99%
“…After this procedure, cDNA was synthesized using the High capacity cDNA Reverse Transcription kit (Ambion, USA) according the manufacturer’s instructions. Real-time PCRs were performed for the HERV-W, - K and the endogenous gene using the primers and conditions used previously by Nali et al [12] using the Sybr Green method. The primers used are described in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…The heterochromatin loss model is a fundamental genetic mechanism underlying most of the changes in gene expression observed with senescence ( 92 ). Importantly, HERV expression level in babies is low ( 93 ), but increases considerably in older adults and older people ( 83 ). Importantly, most neurodegenerative and autoimmune diseases also occur in older people ( 94 ).…”
Section: Factors That Contribute For Hervs Expressionmentioning
confidence: 99%